Consumption Inequality and the Frequency of Purchases - Olivier Coibion; Yuriy Gorodnichenko; Dmitri Koustas (Institute of Labor Economics (IZA), 2017)
We document a decline in the frequency of shopping trips in the U.S. since 1980 and consider its implications for the measurement of consumption inequality. A decline in shopping frequency as households stock up on storable goods (i.e. inventory behavior) will lead to a rise in expenditure inequality when the latter is measured at high frequency, even when underlying consumption inequality is unchanged. We find that most of the recently documented rise in expenditure inequality in the U.S. since the 1980s can be accounted for by this phenomenon. Using detailed micro data on spending which we link to data on club/warehouse store openings, we directly attribute much of the reduced frequency of shopping trips to the rise in club/warehouse stores.
Keywords: D31; E21; D63; 330; consumption inequality; expenditure inequality